UJI AKTIVITAS JAMU GENDONG KUNYIT ASAM (Curcuma domestica Val.; Tamarindus indica L.) SEBAGAI ANTIDIABETES PADA TIKUS YANG DIINDUKSI STREPTOZOTOCIN - ., Rizqa Ayunda (Jurnal Mahasiswa Farmasi Fakultas Kedokteran dan Ilmu Kesehatan UNTAN, 2014)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia. Jamugendong kunyit asam (Curcuma domestica Val.; Tamarindus indica L.) is a traditional medicine that has antioxidant activity which can contribute to diabeticbecause of the phenolic content. This aim of this study is to determine the effect of jamu gendong kunyit asam on lowering blood glucose levels and repairingdamage of the islet cells. 25 male wistar rats (Rattus norvegicus) were divided into five groups. Group I as a normal group without any treatment, group II, III,IV and V were induced with streptozotocin (7 mg/ 200gBB) then treated with Â CMC 1%, glibenclamide (0.27 mg / 200gBB), jamu gendong kunyit asam 1.90ml/ 200gBB and 3.80 ml/ 200gBB. The treatment was done for 28 days.Glucometer was used to measure the gloucose blood level on day 4, 8, 12, 16, 20,24 and 28. The damages on the islet cells were examined under the microscope onthe histology sample of pancreas prepared with Hematoxyllin eosin stain. Dataswere analyzed statistically with One Way Anova test, T-Test, and the KruskalWallistest using SPSS 17.0 for Windows. Results showed there is a significantdifference (p> 0.05) in blood glucose levels and damage to the islets ofLangerhans of the pancreas between the glibenclamide group and treatment ofjamu gendong kunyit asam. From the research it can be concluded that the jamugendong kunyit asam have antidiabetic activity which isÂ showed by a decrease inblood glucose levels and an improvement of pancreatic islets of Langerhans instreptozotocin-induced diabetic rats with an effective dose of 1.90 ml / 200gBB. Keywords: Diabetes, streptozotocin, jamu gendong kunyit asam, blood glucose, pancreatic histology